2020
DOI: 10.1039/d0ta05372d
|View full text |Cite
|
Sign up to set email alerts
|

Facile ex situ formation of a LiF–polymer composite layer as an artificial SEI layer on Li metal by simple roll-press processing for carbonate electrolyte-based Li metal batteries

Abstract: Lithium (Li) metal has been considered as an ideal anode for next-generation Li metal batteries (LMBs). However, Li dendrite formation and low Coulombic efficiency (CE) are major obstacles for the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…It has been reported that LiF/defluorinated polymers SEI can be obtained by continuous roll-press 24 , but the reaction mechanism is still not clear. Differently, in our case, only an inducing force is needed to start the reaction without any other physical and chemical processes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that LiF/defluorinated polymers SEI can be obtained by continuous roll-press 24 , but the reaction mechanism is still not clear. Differently, in our case, only an inducing force is needed to start the reaction without any other physical and chemical processes.…”
Section: Resultsmentioning
confidence: 99%
“…As for the control sample, the peaks at 685.2 eV and 686.3 eV can be assigned to the compound of LiF and C-F. It is obvious that an increased proportion of LiF is obtained on the modified Cu, which is essential for uniform and stable SEI [27,28] .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 91%
“…Perhaps the most straightforward top-down approach of engineering an Art-SEI is the application of a powder layer and subsequent fixation by mechanical pressure. [136][137][138] This is especially viable for Li metal since its softness favors the embedding of particles. Goodenough's group loaded Li 3 N as well as Al 2 O 3 particles on Li foil and subjected to a rollpressing procedure, see Figure 6a,b.…”
Section: Pressingmentioning
confidence: 99%
“…Sun et al prepared a LiF-polymer composite layer (LiF@ Po) by roll-pressing polytetrafluoroethylene (PTFE) onto Li metal. [138] The interphase between PTFE and Li is proposed to form a LiF layer, while further inside the PTFE a polymeric layer is built. Both these layers remain on the Li surface as the PTFE film is detached.…”
Section: Pressingmentioning
confidence: 99%